1994
DOI: 10.1063/1.357273
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of gallium nitride

Abstract: Lattice constants of gallium nitride (wurzite structure) have been measured at temperatures 294–753 K. The measurements were performed by using x-ray diffractometry. Two kinds of samples were used: (1) bulk monocrystal grown at pressure of 15 kbar, (2) epitaxial layer grown on a sapphire substrate. The latter had a smaller lattice constant in a direction parallel to the interface plane by about 0.03%. This difference was induced by a higher thermal expansion of the sapphire with respect to the GaN layer. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(81 citation statements)
references
References 6 publications
7
74
0
Order By: Relevance
“…15 We found that the two a lattice parameters are smaller than the strain-free value 31 as one can expect from the difference of the thermal expansion coefficients between GaN and sapphire. 39 The distortion of the GaN basal plane under such an anisotropic compressive strain is illustrated in Fig. 1͑c͒.…”
Section: A Anisotropic Strainmentioning
confidence: 99%
“…15 We found that the two a lattice parameters are smaller than the strain-free value 31 as one can expect from the difference of the thermal expansion coefficients between GaN and sapphire. 39 The distortion of the GaN basal plane under such an anisotropic compressive strain is illustrated in Fig. 1͑c͒.…”
Section: A Anisotropic Strainmentioning
confidence: 99%
“…The difference of the thermal expansion coefficients ͑TEC͒ of the substrate and the epitaxial layer can account for the compressive stress found for the undoped sample. 17,18 This leads to the conclusion that the deposited layers were fully relaxed or only slightly stressed during the growth. The incorporation of Si into the layer not only leads to strain relaxation, as generally considered, but also induces tensile strain in the layer.…”
Section: A Xrdmentioning
confidence: 99%
“…Among others, the stress relaxation in Si-doped GaN and undoped GaN films has been the focus of a number of recent studies. 4,[9][10][11] The effect of silicon doping on the mechanism of stress relaxation and defect formation in GaN is still under discussion. Ruvimov et al 4 suggest that the thermal stress is partly relaxed by migration of threading dislocations, leaving additional misfit dislocations in the basal plane.…”
Section: Introductionmentioning
confidence: 99%
“…An additional complication arises for AlGaN grown on sapphire, the most common substrate of choice, as the sapphire (linear thermal expansion coefficient α ~ 7.6x10 -6 k -1 ) exerts a compressive strain to the AlGaN layers (α ~ 5.6x10 -6 k -1 ) during cool down which tends to mask the grown-in tensile strain due to lattice mismatch. Most of the post-growth ex-situ strain characterizations [8][9][10][11][12][13] would in this case measure a combination of a tensile stress due to lattice mismatch and a compressive component due to thermal expansion mismatch. In an attempt to isolate these two competing factors by directly probing the grown-in strain, we have employed an in-situ stress/strain monitor based on wafer-curvature measurement [14].…”
Section: Introductionmentioning
confidence: 99%